PENGARUH TERAPI KOGNITIF PERILAKUAN UNTUK MENURUNKAN GANGGUAN PERILAKU MENENTANG PADA SISWA MTS X DI YOGYAKARTA - Wahyu Kurniawan (Society, 2016)
This study aimed to determine the effect of Cognitive Therapy Behavioral to reduce behavioral disorders opposed. Hypothesis proposed in this study is that there is a difference frequency between the opposing behavioral disorders before and after cognitive therapy to students behavioral MTS X in Yogyakarta. Subjects were given cognitive therapy behavioral decreased frequency of behavioral disorders in school against. Subjects in the study of 4 students of class X MTS 8. The design used in this study was a single case study in the form of cognitive therapy behavioral influence. The method of analysis used analysis, visual inspection, interview and observation and analysis of non-parametric (Wilcoxon). The results of hypothesis testing in this therapy is Z for = 0.034 (p> 0.05), Based on the analysis means that there are differences in the frequency of behavioral disorders oppose decrease between before and after cognitive therapy behavioral on MTS X grade 8 students in Yogyakarta.